Karakterisasi Mutu Kimia, Sensori, dan Mikrobiologis Ikan Peda di Pasar Tradisional dan Pasar Modern - Finna Aura Ramadhani; Adriana Monica Sahidu; Veryl Hasan (Program Studi Teknologi Hasil Pertanian Fakultas Sains dan Teknologi Hasil Pertanian Universitas Muhammadiyah Sidenreng Rappang, 2026)
Peda fish is a product of traditional fermentation with the addition of 20-30% salt. The quality of peda fish needs attention considering that the production and distribution processes are still simple and conventional. This study aims to determine the chemical, sensory, and microbiological characteristics of peda fish. This research used peda fish samples obtained from traditional and modern markets in the city of Surabaya. The samples were observed for water content, acid-insoluble ash, salt, sensory properties (appearance, aroma, and texture), and Total Plate Count (TPC). The results showed that only one out of six peda fish samples met the requirements of SNI 8273:2023 for water content. The acid-insoluble ash content of all samples did not meet the requirements of SNI 8273:2023. The salt content, sensory properties, and Total Plate Count (TPC) of all peda fish samples were found to meet the requirements of SNI 8273:2023.